Second Ilga pink book : a global view of lesbian and gay liberation and oppression. - International Lesbian and Gay Association (Utrecht : Interfacultaire Werkgroep Homostudies Rijksuniversiteit Utrecht, 1988)
Fonds Suzan Daniel (FSD)
Engels
Monografie